Programa Nacional de Integração da Educação Profissional com a Educação Básica na Modalidade de Educação de Jovens e Adultos (PROEJA): reflexões acerca do trabalho como princípio educativo. - Yamanoe, Mayara Cristina Pereira (2011)
This study aimed to confront the work as an educational principle in PROEJA - National Program for Integration of Professional Education with Basic Education in the Mode of Education, Youth and Adult. To meet this objective, we seek to chart a course of education policy brief focused on Professional Education and Youth and Adult Education in Brazil, presenting the historical and political elements that led to the deployment of PROEJA; relationships between work and education categories, explaining how they are in capitalist society, understanding work on Gramsci as an educational principle, such a conception in the questioning PROEJA, indicating the limits and possibilities of linking the PROEJA this principle. The work consists of two chapters, the first refers specifically to PROEJA, its implementation and a brief historical education about the modalities that originated - Professional Education and Youth and Adult Education. The second chapter discusses the debate on the relationship between work and education in capitalist society, has the Gramscian concept of work as an educational principle and reflects on the adoption of this principle by PROEJA, seeking to problematize it in order to understand what the limits and the possibilities realization of this conception in the current mode of production.